Cognitive Load Circumstance of Tourism Vocational Students in Mathematics Learning - Gusti Ayu Dessy Sugiharni; Firlie Lanovia Amir (Universitas Pendidikan Ganesha, 2025)
This study aimed to describe the cognitive load circumstance of grade XI students in the odd semester of SMK Pariwisata Budaya Bedulu. The research method used was a qualitative descriptive approach. Data collection used observation, interview, and test techniques. Data were analyzed using Triangulation analysis techniques. This study used a sample of three students, each with high, medium, and low mathematical abilities. The research results indicate that students' cognitive load needs special attention. The condition of students' intrinsic and extraneous cognitive load was high, in contrast to the low Germane cognitive load of students. Teachers can minimize students' cognitive load by updating devices, media, and learning techniques so they do not feel burdened when implementing mathematics learning.